"Turn-of-the-Nut" Method Is Not Appropriate for Use in Cancellous Bone. Issue 11 (November 2015) - Ryan, Melissa K.; Mohtar, Aaron A.; Costi, John J.; Reynolds, Karen J.
Abstract : Objective: The level to which bone screws are tightened is determined subjectively by the operating surgeon. It is likely that the tactile feedback that surgeons rely on is based on localized tissue yielding, which may predispose the screw–bone interface to failure. A limited number of studies have investigated the ratio between clinical tightening torque and stripping torque. The purpose of this study was to measure, for the first time, the ratio between yield torque (Tyield ) and stripping torque (Tmax ) during screw insertion into the cancellous bone and to compare these torques with clinical levels of tightening reported in the literature. Additionally, a rotational limit was investigated as a potential end point for screw insertion in cancellous bone. Methods: A 6.5-mm outer diameter commercial cancellous bone screw was inserted into human femoral head specimens (n = 89). Screws were inserted to failure, while recording insertion torque, compression under the screw head, and rotation angle. Results: The median, interquartile ranges, and coefficient of variation were calculated for each of the following parameters: Tyield, Tmax, Tyield /Tmax, slope, Tplateau, and rotation angle. The median ratio of Tyield /Tmax and rotation angle was 85.45% and 96.5 degrees, respectively. The coefficient of variation was greatest for the rotation angle compared with the ratio of Tyield /Tmax (0.37 vs. 0.12). Conclusions: The detection of yield may be a more precise method than the rotation angle in cancellous bone; however, bone–screw constructs that exhibit a Tyield close to Tmax may be more susceptible to stripping during insertion. Future work can identify factors that influence the ratio of Tyield /Tmax may help to reduce the incidence of screw stripping.